Changes in functional balance and falls in patients with chronic migraine, migraine with and without aura - Carvalho, Gabriela Ferreira; Silva, C. A.; Florencio, L. L.; Pinheiro, C. F.; Dach, F.; Bevilaqua-Grossi, D (Headache Medicine, 2017)
Short Communication